Europium-151 and iron-57 nuclear resonant vibrational spectroscopy of naturally abundant KEu(iii)Fe(ii)(CN)6 and Eu(iii)Fe(iii)(CN)6 complexes. Issue 46 (8th November 2022) - Wang, Hongxin; Huang, Songping D.; Yan, Lifen; Hu, Michael Y.; Zhao, Jiyong; Alp, Ercan E.; Yoda, Yoshitaka; Petersen, Courtney M.; Thompson, Matthew K.
Abstract : We have performed and analyzed the first combined 151 Eu and 57 Fe nuclear resonant vibrational spectroscopy (NRVS) for naturally abundant KEu(iii )[Fe(ii )(CN)6 ] or Eu(iii )[Fe(iii )(CN)6 ] complex. Abstract : We have performed and analyzed the first combined 151 Eu and 57 Fe nuclear resonant vibrational spectroscopy (NRVS) for naturally abundant KEu(iii )[Fe(ii )(CN)6 ] and Eu(iii )[Fe(iii )(CN)6 ] complexes. Comparison of the observed 151 Eu vs. 57 Fe NRVS spectroscopic features confirms that Eu(iii ) in both KEu(iii )[Fe(ii )(CN)6 ] and Eu(iii )[Fe(iii )(CN)6 ] occupies a position outside the [Fe(CN)6 ] core and coordinates to the N atoms of the CN − ions, whereas Fe(iii ) or Fe(ii ) occupies the site inside the [Fe(CN)6 ] 4− core and coordinates to the C atoms of the CN − ions. In addition to the spectroscopic interest, the results from this study provide invaluable insights for the design and evaluation of the nanoparticles of such complexes as potential cellular contrast agents for their use in magnetic resonance imaging. The combined 151 Eu and 57 Fe NRVS measurements are also among the first few explorations of bi-isotopic NRVS experiments.